Physical and sensorial properties of potato breads fortified with whole soybean flour - Dorina Isabel Gomes Natal (Revista Chilena de Nutrición, 2013)
The aim of this work was to study the effects of fortification of potato bread with whole soybean flour on their physicochemical and sensory properties. Control formulations containing 30%, 50% and 70% soybean flour were developed. Firmness, cohesiveness, gumminess and chewiness of bread increased with the addition of whole soybean flour. The contents of protein, dietary fiber and minerals calcium, zinc, magnesium, copper and phosphorus increased with elevated concentration of soybean flour, while the lipid profile was unchanged. Preference mapping indicated greater acceptance of the control and 30% whole soybean flour formulations. These results were correlated to texture and showed that the greater firmness negatively affected its acceptance. It was concluded that the formulation with 30% was the best option offering good acceptance and high content of nutrients, which makes the flour substitution a viable alternative for the preparation of fortified baking products with equal sensory and physicochemical quality.